Political Parties and the Party System - Botterill, L.; Fenna, Alan (Pearson Australia, 2013)
Political parties are an important, indeed almost ubiquitous, feature of liberal-democracy systems of government. Political parties provide a focal point for voters, who can channel their vote on the basis of a broad understanding of what a candidate stands for and how he or she will vote in the Parliament on particular issues. Although generally unloved, parties are an essential and unavoidable part of the political system. A great deal depends on parties in a liberal democracy: as the vehicle through which individuals achieve and hold office, they are the key link between citizens and government. There are several characteristics of the Australian political party system that distinguish it from party systems elsewhere in the developed world and make it worthy of study in its own right. One of these characteristics is that Australia was the first democratic nation to be led by a party representing labour-a development that provoked the rapid organisation of the 'non-Labor' parties in Australia (see Chapter 11). Second, Australia has the last remaining agrarian party in the developed world. Third, the Australian electoral system has almost always generated strong majority governments at national level. And fourth, the coalition between the Liberal Party and the National Party is an oddity among coalition arrangements. This chapter provides an overview of the factors that make the Australian party system distinctive and puts these features in the context of the international party politics literature, which, in general, has been weak in its analysis of the Australian party landscape.